2020
DOI: 10.5051/jpis.2020.50.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2 techniques of epithelial removal in subepithelial connective tissue graft surgery: a comparative histological study

Abstract: Purpose: Subepithelial connective tissue grafts (SCTGs) are commonly performed for the treatment of gingival recession due to their high predictability. This study evaluated and histologically compared connective tissue grafts in terms of the presence of epithelial remnants and composition of the tissue types that were present (epithelium, lamina propria, and submucosa). Methods: Ten patients underwent epithelium removal using 2 different techniques: the use of a blade (group B) and through abrasion (group A).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(28 reference statements)
1
8
2
Order By: Relevance
“…The graft was de-epithelialized with a 15c blade to enable better visualization and ensure complete removal of epithelium, which was consistent with a recent report showing no significant difference between de-epithelialization using blade or abrasion. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…The graft was de-epithelialized with a 15c blade to enable better visualization and ensure complete removal of epithelium, which was consistent with a recent report showing no significant difference between de-epithelialization using blade or abrasion. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…This figure is slightly lower than the 0.3 mm reported by Zuhr et al (2014), and values between 0.30 mm (first molar area) and 0.41 mm (canine area) have also been reported (Cho et al, 2013). With respect to percentage, other authors have reported that the epithelial layer represented only 1.04% of the palatal mucosa (Marques de Mattos et al, 2019). This discrepancy with our result (6.45%) could be explained by the fact the abrasion technique used by the aforementioned authors presented epithelial remnants in only 20% of their samples.…”
Section: Discussionmentioning
confidence: 94%
“…Previous histological evaluations showed that 80% of PI grafts (24/30) (Harris, 2003) and 100% of DE grafts (5/5) presented epithelial remnants (Azar et al, 2019). Other forms of reducing epithelial remnants are high‐speed diamond burs (abrasion) (Marques de Mattos et al, 2020) or high‐level laser Er: YAG (Grzech‐Leśniak et al, 2018; Gursoy et al, 2019), Er, Cr: YSSG (Lin et al, 2018), Nd: YAG (Keskiner et al, 2016 aluminium, gallium and arsenide diode laser (Ozcelik, Seydaoglu, & Haytac, 2016). Thus, the amount of epithelial tissue remnant in grafts necessary to the development of cysts, epithelial inclusion and/or discharge release (Harris, 2003) remains unknown.…”
Section: Discussionmentioning
confidence: 99%